Fitorremediación de mercurio a partir de elodea sp - Jaramillo F, María Consuelo (Editorial bonaventuriana, 2018)
Mercury is a contaminant from mining, which is highly toxic to plants, animals and humans. Mercury is bioaccumulated in plants and fish of human consumption. This research evaluated bioremediation capacity of mercury ion by the aquatic macrophyte Elodea sp. Stems of 35-36 cm of plants has been evaluated at different concentrations of HgCl2 solution. The evaluated concentrations were 0,39mg/ml, 1,55mg/ml and of 6,25mg/ml, although the Elodea sp plant showed high performance in the three solutions, but the plant showed 100% of removing of mercury at 1,55mg/ml concentration, therefore this concentration was become in suitable conditions for removing mercury.